2021
DOI: 10.1007/s00420-021-01697-9
|View full text |Cite
|
Sign up to set email alerts
|

Disability pensions related to heavy physical workload: a cohort study of middle-aged and older workers in Sweden

Abstract: Objectives The aim of the study was to examine the associations between heavy physical workload among middle-aged and older workers and disability pension due to any diagnosis, as well as musculoskeletal, psychiatric, cardiovascular or respiratory diagnoses. The population-based design made it possible to examine dose–response and potential gender differences in the associations. Methods About 1.8 million men and women aged 44–63 years and registered as li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 42 publications
4
30
2
1
Order By: Relevance
“…Strenuous physical work has been associated with poorer musculoskeletal health (5) and exit from the labor market, often through DP (6)(7)(8)(9). This study showed that a change to an occupation with lower physical workload was associated with a reduced risk of DP.…”
Section: Interpretation Of Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Strenuous physical work has been associated with poorer musculoskeletal health (5) and exit from the labor market, often through DP (6)(7)(8)(9). This study showed that a change to an occupation with lower physical workload was associated with a reduced risk of DP.…”
Section: Interpretation Of Resultsmentioning
confidence: 59%
“…Workers aged ≥50 years in physically demanding jobs have reported that the imbalance between their physical capacity and job tasks is a factor pushing them out of working life (4). Strenuous physical work such as awkward postures, overall heavy physical workload or heavy lifting has been associated with musculoskeletal disorders (5) and exit from the labor market, often through disability pension (DP) (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Parents SEP † Unskilled 97 608 (33) 92 990 (31) 74 311 (26) 76 304 (25) 54 153 (18) 99 202 (32) 88 136 (31) 73 198 (24) 77 306 (26) 57 524 (20) skilled 60 252 (20) 69 851 (23) 65 592 (23) 66 150 (22) 48 122 (16) 71 468 (23) 73 405 (26) 61 001 (20) 55 910 (19) 48 106 285 (33) 105 466 (31) 91 203 (30) 107 528 (35) 93 709 (32) 102 407 (33) 98 041 (31) 107 570 (35) 92 831 (30) 41-50 101 130 (39) 128 418 (40) 130 433 (39) 117 455 (38) 117 121 (38) 115 156 (39) 114 133 (37) 129 347 (41) 117 189 (39) 118 732 (39) 51-60 73 970 (29) 88 581 (27) 99 200 (30) 97 199 (32) 81 256 (27) 86 909 (29) 91 864 (30) 86 782 (28) 79 403 (26) 95 248 (39) Born outside Sweden…”
Section: Discussionunclassified
“…This study is based on the Swedish Work, Illness, and labour-market Participation (SWIP) cohort which includes all individuals between the ages of 16 and 65 who were registered in Sweden during the baseline year 2005 (around 5.4 million). 18 , 19 Data are linked from several different Swedish administrative and medical registers including the Swedish total population register, the Longitudinal Integrated Database for Health Insurance and Labour Market Studies register (LISA), the Swedish National Patient Register, as well as information from earlier population censuses. These registers have been commended for their accuracy and completeness.…”
Section: Methodsmentioning
confidence: 99%